Spatial and temporal variability in sea surface temperatures and monsoon dynamics in the northwestern Arabian Sea during the last 43 kyr - Maier, Jan; Burdanowitz, Nicole; Schmiedl, Gerhard; Gaye, Birgit (Climate of the Past, 2025)
In this study, we present the first well-dated, high-resolution alkenone-based sea surface temperature (SST) record from the northeastern Oman margin (Gulf of Oman) in the northwestern Arabian Sea. The SST reconstructions from core SL167 span the last 43 kyr and reveal temperature fluctuations of around 7 °C (ranging from 20.1 to 27.4 °C). Thus, this region has a higher sensitivity to climate variations compared to other core locations in the Arabian Sea and fills a gap in a previously unstudied region. SSTs were lowest during Heinrich event 4 (H4) and were comparatively low during H3, H2, the Younger Dryas, and the early and late Holocene. Comparatively higher SST occurred during some Dansgaard-Oeschger interstadials (D-O 11 and D-O 4-9), the Bølling-Allerød (B-A), and the mid-Holocene. The SST was predominantly influenced by the SW monsoon during warmer periods and the NE monsoon during cold intervals. Importantly, the Last Glacial Maximum stands out owing to the absence of intense cooling at the core site which clearly diverges from previously known SST patterns. We speculate that this pattern was caused by stronger NW winds and an eastward shift in the SST gradient in the Gulf of Oman, resulting in a brief and moderate cooling period. Strong SW winds during the early Holocene transported cold-water masses from the Oman upwelling into the Gulf of Oman, lowering SSTs. A rapid temperature increase of approx. 2 °C during the mid-Holocene was likely induced by the weakening of SW winds and an abrupt eastward shift in the SST gradient.
CRIS-Team Scopus Importer:2025-02-14